Solid-state lithium battery
By using metal fluoride and modified metal fluoride composite materials as the positive electrode active substances in solid-state lithium batteries, combined with optimized solid-state electrolyte and interface processing technology, the problems of low safety and insufficient energy density of liquid lithium-ion batteries are solved, and a solid-state lithium battery with high energy density and high safety performance are achieved.
Patent Information
- Application Number
- CN202110335714.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2021-03-29
- Publication Date
- 2025-03-11
- Estimated Expiration
- 2041-03-29
AI Technical Summary
Existing liquid lithium-ion batteries have problems of low safety and high risk, and the energy density of the cathode material is low, making it difficult to meet the market's demand for high energy density and high safety performance.
Metal fluoride and/or modified metal fluoride composite materials are used as the positive electrode active substances, combined with optimized solid-state electrolytes and interface processing technology, solid-state lithium batteries with high energy density and high safety performance are prepared.
It has achieved high energy density of solid-state lithium batteries, with mass energy density up to 500Wh/kg and volume energy density up to 1000Wh/L. It also has excellent high-temperature performance and high safety performance, and has passed safety tests such as needle puncture and overcharge.
Smart Images

Figure BDA0002997477790000111 
Figure BDA0002997477790000121
Abstract
Description
Technical Field
[0001] The present application relates to the field of lithium batteries, and in particular to a solid-state lithium battery whose positive electrode active material comprises metal fluoride. Background Art
[0002] The current liquid lithium-ion battery has only a 10-micron thick separator between the positive and negative electrodes, and the separator has low puncture resistance. As the number of charge and discharge cycles increases, lithium ions are easily precipitated on the negative electrode surface to form lithium dendrites, puncturing the separator, causing an internal short circuit and then catching fire and exploding. Liquid lithium-ion batteries have low safety and high risks.
[0003] The market's performance requirements for batteries are not limited to safety performance, but also increasingly demanding energy density. Currently, the cathode material of lithium-ion batteries has a low specific capacity, and improving its energy density is the most effective way to increase the energy density of lithium batteries. Therefore, there is an urgent need to develop a new generation of batteries with high energy and high safety performance.
[0004] Metal fluorides are a new type of positive electrode material for lithium-ion batteries with advantages such as low cost and high energy density. However, their liquid lithium-ion batteries have disadvantages such as rapid capacity decay, large volume expansion, and side reactions with the electrolyte, making their practical commercial application not easy. Summary of the invention
[0005] In view of the problems existing in the background technology, the object of the present invention is to provide a metal fluoride solid-state lithium battery, which has the advantages of high energy density, excellent high temperature performance and high safety performance.
[0006] In order to achieve the above object, the present invention adopts the following technical solution, and provides a solid-state lithium battery, which includes:
[0007] A positive electrode sheet, a negative electrode sheet and a solid electrolyte layer; the positive electrode sheet contains a positive electrode active material layer; the positive electrode active material of the positive electrode active material layer includes metal fluoride and / or modified metal fluoride composite material.
[0008] Preferably, the metal fluoride is FeF 3 , CoF 3 ,CuF 2 、MnF 3、 、LiFe 2 F 6 and LiMgFeF 6 One or any combination of the .
[0009] Preferably, the modified metal fluoride composite material is a carbon-modified metal fluoride composite material.
[0010] More preferably, the carbon-modified metal fluoride composite material comprises FeF 3 / C、CoF 3 / C、CuF 2 / C and MnF 3 / C or any combination of them.
[0011] The carbon source of the carbon-modified metal fluoride composite material is one or any combination of carbon nanotubes, carbon black, artificial graphite, natural graphite, acetylene black, graphene and carbon-containing organic polymer materials.
[0012] Preferably, the carbon source is one or a combination of carbon nanotubes, carbon black, natural graphite, acetylene black and graphene.
[0013] More preferably, the mass ratio of metal fluoride to carbon in the carbon-modified metal fluoride composite material is 1 to 50:1.
[0014] Preferably, the positive electrode sheet comprises a positive electrode current collector, a conductive agent, a binder and the positive electrode active material layer.
[0015] More preferably, the weight ratio of the conductive agent, the binder and the positive electrode active material layer is (1-10):(1-10):(80-98), preferably (2-5):(1-5):(90-97).
[0016] The conductive agent is one or any combination of conductive carbon black, conductive graphite, conductive carbon nanotubes, graphene and conductive carbon fibers.
[0017] The binder is one or any combination of polyvinylidene fluoride, polytetrafluoroethylene, polyvinyl alcohol, sodium hydroxymethyl cellulose, polyacrylic acid, styrene-butadiene rubber and acrylonitrile.
[0018] Preferably, the positive electrode active material layer further comprises a solid electrolyte, and the content of the solid electrolyte in the positive electrode active material is preferably 0.1-20% by weight.
[0019] Preferably, the solid electrolyte layer comprises a solid electrolyte, and the solid electrolyte is one or more of a lithium sulfide-containing solid electrolyte, a lithium oxide-containing solid electrolyte, and a lithium polymer-containing solid electrolyte.
[0020] Preferably, the lithium-containing sulfide may be a derivative of the elements having different composition ratios; and the lithium-containing oxide may be a derivative of the elements having different composition ratios.
[0021] More preferably, the lithium sulfide-containing solid electrolyte is selected from Li 10 G 2 S 12 ,Li3 PS 4 ,Li 3 Zn 0.5 G JZ 4 , Li 7 P 3 S 11 One or more of the following; the lithium oxide-containing solid electrolyte is selected from Li 2 Al 3 Ge 2 (PO 4 ) 3 , Li 3 La 2 TiO 3 、LiZr 2 Ti(PO 4 ) 3 , Li 2 Al 2 Ti(PO 4 ) 3 and Li 2 TaLa 3 Zr 2 O 12 One or more of the following.
[0022] More preferably, the lithium-containing polymer solid electrolyte is selected from the synthetic product of an organic polymer and a lithium salt, the polymer is one or more of polyethylene oxide (PEO), polyacrylonitrile, polymethyl methacrylate, polycarbonate and polyvinylidene fluoride, or the comonomer is a copolymer of two or more of ethylene oxide, acrylonitrile, methyl methacrylate, carbonate and vinylidene fluoride; the lithium salt is one or more of lithium perchlorate, lithium hexafluorophosphate and lithium bistrifluoromethanesulfonyl imide (LiTFSI); further preferably, the lithium-containing polymer solid electrolyte is selected from the processed synthetic product of polyethylene oxide (PEO) and lithium bistrifluoromethanesulfonyl imide (LiTFSI).
[0023] Preferably, the interior of the positive electrode plate of the lithium battery, the interior of the solid electrolyte layer, between the positive electrode plate and the solid electrolyte layer, and the internal gaps of the battery are also filled with a non-aqueous electrolyte.
[0024] More preferably, the mass content of the non-aqueous electrolyte in the solid-state lithium battery is 0.01-5% by weight.
[0025] Preferably, the negative electrode plate is a metal lithium plate and / or a lithium alloy.
[0026] The solid-state lithium battery of the present invention realizes the application of metal fluorides to solid-state lithium batteries by optimizing the active substance of the positive electrode material, optimizing the solid-state electrolyte, optimizing the interface processing technology, and improving the lithium ion conductivity performance. The solid-state lithium battery of the present invention has high mass specific energy and volume specific energy, and the mass energy density can reach 500Wh / kg and the volume energy density can reach 1000Wh / L.
[0027] The solid-state lithium battery of the present invention has excellent high-temperature performance and does not swell or leak under high-temperature storage.
[0028] The solid-state lithium battery of the present invention has the outstanding advantage of high safety, and 100% passes the safety tests such as needle puncture and overcharge.
[0029] The solid-state lithium battery of the present invention is compatible with most production processes of soft-pack batteries. DETAILED DESCRIPTION
[0030] The specific embodiments of the present invention are described in detail below. It should be understood that the specific embodiments described herein are only used to illustrate and explain the present invention, and are not used to limit the present invention.
[0031] The present invention provides a solid-state lithium battery, which includes: a positive electrode plate, a negative electrode plate and a solid electrolyte; the positive electrode plate contains a positive electrode active material layer; the positive electrode active material of the positive electrode active material layer includes a metal fluoride and / or a modified metal fluoride composite material. The solid-state lithium battery of the present invention adopts the positive electrode active material metal fluoride and / or the modified metal fluoride composite material as the positive electrode active material, so that the prepared solid-state lithium battery has advantages such as high mass specific energy and volume specific energy, and the mass energy density can reach 500Wh / kg, for example, and the volume energy density can reach 1000Wh / L, for example.
[0032] The present invention has found that the reaction between metal fluorides and metallic lithium is different from the insertion and extraction reaction of traditional lithium-ion batteries. Metal fluorides can not only undergo lithium ion insertion and extraction reactions, but can also undergo chemical conversion reactions with lithium metal to store energy. As the positive electrode material of solid-state lithium batteries, metal fluorides have a capacity far higher than that of layered transition metal oxides or spinel lithium manganese oxide materials.
[0033] According to the present invention, the metal fluoride has a wide range of optional types. For the present invention, the metal fluoride is preferably FeF 3 , CoF 3 ,CuF 2 、MnF 3 、LiFe 2 F 6 and LiMgFeF 6 One or any combination of the .
[0034] According to the present invention, research has found that for solid-state lithium batteries, in order to improve the electrochemical properties of metal fluorides, carbon materials are used to modify metal fluorides; according to the present invention, the preferred carbon source is one or any combination of carbon nanotubes, carbon black, artificial graphite, natural graphite, acetylene black, graphene, and carbon-containing organic polymer materials.
[0035] According to the present invention, preferably the carbon-modified metal fluoride composite material comprises FeF 3 / C、CoF 3 / C、CuF 2 / C and MnF 3 / C; more preferably, the mass ratio of metal fluoride to carbon in the carbon-modified metal fluoride composite material is 1 to 50: 1. The aforementioned carbon-modified metal fluoride composite material has better electrochemical properties and better conductivity when applied to solid-state lithium batteries, and has better synergistic effects with other materials in solid-state lithium batteries, thereby enhancing the cycle performance of solid-state lithium batteries.
[0036] According to a preferred embodiment of the present invention, the preferred modification step includes: the mass ratio of metal fluoride to carbon source is 1 to 50:1, and ball milling is performed under a nitrogen or argon atmosphere for 3 to 30 hours.
[0037] According to the present invention, the solid electrolyte has a wide range of optional types. For the present invention, the solid electrolyte is preferably one of a lithium sulfide-containing solid electrolyte, a lithium oxide-containing solid electrolyte and a lithium polymer-containing solid electrolyte.
[0038] According to the present invention, preferably, the lithium-containing sulfide may be a derivative having different component ratios of the elements; more preferably, the lithium-containing sulfide solid electrolyte is selected from Li 10 G 2 S 12 ,Li 3 PS 4 ,Li 3 Zn 0.5 G JZ 4 ,Li 7 P 3 S 11 One or more of the above-mentioned lithium sulfide solid electrolyte has the advantages of being stable to metallic lithium, having high conductivity and a wide electrochemical window.
[0039] According to the present invention, preferably, the lithium-containing oxide may be a derivative having different component ratios of the elements thereof; more preferably, the lithium-containing oxide solid electrolyte is selected from Li 2 Al 3 Ge2 (PO 4 ) 3 , Li 3 La 2 TiO 3 、LiZr 2 Ti(PO 4 ) 3 , Li 2 Al 2 Ti(PO 4 ) 3 and Li 2 TaLa 3 Zr 2 O 12 The use of the above-mentioned lithium oxide-containing solid electrolyte has the advantages of being stable to metallic lithium, having high conductivity and a wide electrochemical window.
[0040] According to the present invention, preferably, the lithium-containing polymer solid electrolyte is selected from the synthetic product of an organic polymer and a lithium salt, wherein the polymer is one or more of polyethylene oxide (PEO), polyacrylonitrile, polymethyl methacrylate, polycarbonate, and polyvinylidene fluoride, or the comonomer is a copolymer of two or more of ethylene oxide, acrylonitrile, methyl methacrylate, carbonate, and vinylidene fluoride; the lithium salt is one or more of lithium perchlorate, lithium hexafluorophosphate, and lithium bistrifluoromethanesulfonyl imide (LiTFSI); more preferably, it is selected from the synthetic product of polyethylene oxide (PEO) and lithium bistrifluoromethanesulfonyl imide (LiTFSI). The use of the aforementioned lithium-containing polymer solid electrolyte has the advantages of being stable to metallic lithium, having high conductivity, and having a wide electrochemical window.
[0041] According to the present invention, the positive electrode sheet preferably includes a positive electrode current collector, a conductive agent, a binder and the positive electrode active material layer.
[0042] According to a preferred embodiment of the present invention, based on the total weight of the positive electrode active material, the positive electrode conductive agent and the positive electrode binder, the weight ratio of the conductive agent, the binder and the positive electrode active material layer is preferably (1-10): (1-10): (80-98), and more preferably (2-5): (1-5): (90-97). The aforementioned ratio can further improve the cycle performance of the solid-state lithium battery.
[0043] According to the present invention, the type and content of the conductive agent can be conventionally selected in the art. Preferably, the conductive agent is one or any combination of conductive carbon black, conductive graphite, conductive carbon nanotubes, graphene and conductive carbon fibers.
[0044] According to the present invention, the type and content of the negative electrode binder can be conventionally selected in the art. Preferably, the binder is one or any combination of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), polyvinyl alcohol (PVA), sodium hydroxymethyl cellulose (CMC), polyacrylic acid (PAA), styrene-butadiene rubber (SBR) and acrylonitrile (LA132).
[0045] In order to ensure the transmission of lithium ions in the positive electrode active material layer, according to the present invention, it is preferred that the positive electrode active material layer also includes a solid electrolyte. The type of the solid electrolyte is not specifically limited and can be selected according to actual needs. Preferably, the solid electrolyte in the positive electrode active material layer is the same as the type of the solid electrolyte layer disposed between the positive electrode plate and the negative electrode plate. According to a preferred embodiment of the present invention, the content of the solid electrolyte in the positive electrode active material layer is preferably 0.1-10% by weight. The aforementioned preferred embodiment can further improve the cycle performance and safety performance of the solid-state lithium battery.
[0046] In order to reduce the interface impedance between the solid electrolyte and the positive electrode plate and improve the transmission capacity of lithium ions, according to the present invention, preferably, the inside of the positive electrode plate of the solid-state lithium battery, the inside of the solid electrolyte layer, between the positive electrode plate and the solid electrolyte layer, and the internal gap of the battery are also filled with a non-aqueous electrolyte; more preferably, the mass content of the non-aqueous electrolyte in the solid-state lithium battery is 0.01-5 weight%; by using the non-aqueous electrolyte with the aforementioned mass content, the solid-state lithium battery can have higher safety performance while ensuring the electrochemical performance of the solid-state lithium battery.
[0047] According to the present invention, preferably, the non-aqueous electrolyte contains a carbonate solvent and a lithium salt.
[0048] According to the present invention, preferably, the carbonate solvent is at least one of dimethyl carbonate (DMC), ethyl methyl carbonate (EMC), diethyl carbonate (DEC), ethylene carbonate (EC) and propylene carbonate (PC); the lithium salt is LiPF 6 ,LiClO 4 ,LiBF 4 ,LiAsF 6 At least one of the above.
[0049] According to the present invention, the types of the negative electrode plates can be selected from a wide range, and commonly used negative electrode plates can be used in the present invention. For the present invention, the negative electrode plates are preferably selected from metal lithium plates and negative electrode plates made of lithium alloys, and are more preferably metal lithium plates. Compared with lithium alloys, the use of metal lithium plates as negative electrode plates can increase the operating voltage of solid-state lithium batteries, thereby increasing the energy density.
[0050] The present invention will be described in detail below by way of examples, but the scope of the present invention is not limited thereby.
[0051] Example 1
[0052] FeF 3 The powder (D50 = 4.5 um) is mixed with a conductive agent carbon nanotube (LB116-32) and a binder (PVDF 5130) in a mass ratio of 90%:5%:5%, and N-methylpyrrolidone (NMP) is added and stirred to disperse evenly to prepare a coating slurry; the slurry is coated on a positive electrode current collector aluminum foil, dried at 120° C., and rolled to prepare a positive electrode sheet.
[0053] In an argon glove box, lithium foil (thickness = 50 um), solid electrolyte Li 7 La 3 Zr 2 O 12 A film (thickness = 25 um) and a positive electrode sheet (thickness = 30 um) were formed, and finally a pressure of 1 MPa was applied to prepare a solid-state lithium battery.
[0054] Example 2
[0055] FeF 3 Powder (D50 = 4.5um) and conductive carbon black (BET = 210m 2 / g) were mixed at 85g:2.5g, and after ball milling for 6h, solid electrolyte Li 7 La 3 Zr 2 O 12 (D50 = 50 nm) 2.5 g, further ball milled for 6 h, to obtain FeF containing solid electrolyte 3 / C positive electrode active material.
[0056] The positive electrode material is mixed with a conductive agent carbon nanotube (LB116-32) and a binder (PVDF 5130) at a mass ratio of 90%:5%:5%, and N-methylpyrrolidone (NMP) is added and stirred to disperse evenly to prepare a coating slurry; the slurry is coated on a positive electrode current collector aluminum foil, dried at 120°C, and rolled to prepare a positive electrode sheet.
[0057] In an argon glove box, lithium foil (thickness = 50 um), solid electrolyte Li 7 La 3 Zr 2 O 12A film (thickness = 25 um) and a positive electrode sheet (thickness = 30 um) were formed, and finally a pressure of 1 MPa was applied to prepare a solid-state lithium battery.
[0058] Example 3
[0059] FeF 3 Powder (D50 = 4.5um) and conductive carbon black (BET = 210m 2 / g) were mixed at 85g:2.5g, and after ball milling for 6h, solid electrolyte Li 7 La 3 Zr 2 O 12 (D50 = 50 nm) 2.5 g, further ball milled for 6 h, to obtain FeF containing solid electrolyte 3 / C positive electrode active material.
[0060] The positive electrode material is mixed with a conductive agent carbon nanotube (LB116-32) and a binder (PVDF 5130) at a mass ratio of 90%:5%:5%, and N-methylpyrrolidone (NMP) is added and stirred to disperse evenly to prepare a coating slurry; the slurry is coated on a positive electrode current collector aluminum foil, dried at 120°C, and rolled to prepare a positive electrode sheet.
[0061] In an argon glove box, lithium foil (thickness = 50 um), solid electrolyte Li 7 La 3 Zr 2 O 12 The film (thickness = 25um), and the positive electrode (thickness = 30um), add 0.1ml of electrolyte (the mass ratio of electrolyte to solid lithium battery is 5wt%) to the round-type battery measurement kit to make the positive electrode and solid electrolyte film wet. The solvent of the electrolyte is ethylene carbonate EC and dimethyl carbonate DMC (liquid volume ratio is 1:1), and the electrolyte is lithium hexafluorophosphate (LiPF 6 )(1.2mol / L), and finally applied a pressure of 1MPa to prepare a solid-state lithium battery.
[0062] Example 4
[0063] The difference from Example 3 is that the FeF 3 Replaced with CuF 2 ;
[0064] The other operations are the same as those in Example 3.
[0065] Example 5
[0066] The difference from Example 3 is that the FeF 3 Replacement with CoF 3 ;
[0067] The other operations are the same as those in Example 3.
[0068] Example 6
[0069] Compared with implementation 3, the positive electrode active material does not contain a solid electrolyte;
[0070] FeF 3 Powder (D50 = 4.5um) and conductive carbon black (BET = 210m 2 / g) were mixed at 85g:2.5g and ball milled for 6h to obtain FeF 3 / C positive electrode active material;
[0071] The other operations are the same as those in Example 3.
[0072] Example 7
[0073] Different from Example 3, the mass ratio of the positive electrode material, the conductive agent carbon nanotubes (LB116-32), and the binder (PVDF5130) is 85%:8%:7%;
[0074] Other operations are the same as in Example 3.
[0075] Example 8
[0076] Different from Example 3, the solid electrolyte is Li 10 G 2 S 12 , the solid electrolyte membrane is Li 10 G 2 S 12 film;
[0077] Other operations are the same as in Example 3.
[0078] Example 9
[0079] The difference from Example 3 is that the FeF 3 Switching to LiFe 2 F 6 ;
[0080] The other operations are the same as those in Example 3.
[0081] Example 10
[0082] Polyethylene oxide (PEO) and lithium hexafluorophosphate (LiPF 6) and organic solvent 1,3-dioxolane were mixed in a ratio of 80g:20g:30g and ball-milled for 6 hours under nitrogen protection. Part of the raw materials after sufficient ball milling were put into a mold for hot extrusion to obtain a semi-transparent film containing a polymer solid electrolyte with a thickness of 25um.
[0083] In addition, part of the above raw materials after ball milling were mixed with FeF 3 Powder (D50 = 4.5um) and conductive carbon black (BET = 210m 2 / g) were mixed in the ratio of 5.0g:90g:5.0g and ball milled for 6h. The mixed slurry was coated on the positive electrode current collector aluminum foil, dried at 120°C, and rolled to form a positive electrode sheet (thickness = 30um).
[0084] In an argon glove box, lithium foil (thickness = 50 um), a translucent film of the aforementioned polymer solid electrolyte (thickness = 25 um), and a positive electrode sheet (thickness = 30 um) were placed in sequence on an EQ-PSC cylindrical battery measurement kit (diameter 15 mm), and finally a pressure of 1 MPa was applied to prepare a solid-state lithium battery.
[0085] Embodiment 11
[0086] The difference from Example 3 is that the FeF 3 Replaced with MnF 3 ;
[0087] The other operations are the same as those in Example 3.
[0088] Comparative Example 1
[0089] In an argon glove box, the positive electrode sheet in Example 1 and the electrolyte in Example 3 were used to assemble a button cell with a diaphragm (porous polypropylene material with a thickness of 25 μm) and a lithium metal sheet.
[0090] Test Case
[0091] Electrochemical performance test
[0092] The solid-state lithium batteries of Examples 1 to 10 and the button-type battery of Comparative Example 1 were tested in a charge and discharge mode using a charge and discharge instrument, with a charge cut-off voltage of 4.5 V, a discharge cut-off voltage of 1.0 V, a test current density of the active material of 100 mAh / g, and a test temperature of 25° C. The discharge capacity of the active material after the first and 50th weeks of charge and discharge was obtained, as shown in Table 1.
[0093] Acupuncture experiment
[0094] The solid-state lithium batteries of Examples 1-10 and the button battery of Comparative Example 1 were subjected to a needle puncture test. The battery was charged to 4.5V, and a φ3mm high-temperature resistant steel needle was used to vertically pierce the battery at a speed of 5mm / s. The penetration position was preferably close to the geometric center of the pierced surface, and the steel needle stayed in the battery cell. The temperature change on the battery surface and the phenomenon of smoke and fire were observed. The results are shown in Table 1.
[0095] Overcharge test
[0096] The solid-state lithium batteries of Examples 1-10 and the button-type battery of Comparative Example 1 were subjected to an overcharge test. The batteries were charged to 5.5 V, and then charging was stopped to observe the temperature change on the battery surface and the phenomenon of smoke and fire. The results are shown in Table 1.
[0097] High temperature testing
[0098] The solid-state lithium batteries of Examples 1-10 and the button-type battery of Comparative Example 1 were subjected to high temperature tests. After the batteries were charged to 4.5V, they were placed in a high temperature test chamber and heated from room temperature to 130°C at 5°C / min and maintained for 30 minutes. The temperature changes on the battery surface and the phenomenon of smoke and fire were observed. The results are shown in Table 1.
[0099] Table 1 Test results
[0100]
[0101]
[0102] As shown in Table 1, the solid-state lithium battery in Examples 1-11 of the present invention improves lithium ion conductivity by optimizing the positive electrode material active material, optimizing the solid electrolyte, optimizing the interface processing technology, and realizing a solid-state lithium battery with metal fluoride and modified metal fluoride as the positive electrode active material. The solid-state lithium battery does not swell or leak under high-temperature storage, and 100% passes the acupuncture and overcharge safety tests. This shows a good technical improvement direction and practical application prospects.
[0103] Compared with Example 2 and Example 3, the electrode of Example 3 contains a wet solid electrolyte, the impedance polarization in the battery is greatly reduced, the lithium ion conductivity is improved, and the discharge capacity and cycle capacity retention rate are improved, but there is no smoke or fire in the safety test items.
[0104] Compared with Example 3, Example 6 does not contain a solid electrolyte in the positive electrode active material layer, and its discharge capacity and cycle capacity retention rate are reduced, but it does not smoke or catch fire in the safety test items.
[0105] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various specific technical features in any suitable manner. In order to avoid unnecessary repetition, the present invention will not further describe various possible combinations. However, these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.
Claims
1. A solid-state lithium battery, characterized in that: The lithium battery comprises: a positive electrode sheet, a negative electrode sheet and a solid electrolyte layer; the positive electrode sheet comprises a positive electrode active material layer; the positive electrode active material of the positive electrode active material layer comprises a modified metal fluoride composite material; the modified metal fluoride composite material is a carbon-modified metal fluoride composite material, and the metal fluoride is one or any combination of FeF3, CoF3, CuF2, MnF3, LiFe2F6 and LiMgFeF6; The positive electrode active material layer also includes a solid electrolyte, and the content of the solid electrolyte in the positive electrode active material is 0.1-20% by weight.
2. The solid-state lithium battery according to claim 1, wherein: The carbon-modified metal fluoride composite material comprises one or any combination of FeF3 / C, CoF3 / C, CuF2 / C and MnF3 / C.
3. The solid-state lithium battery according to claim 1 or 2, wherein: The carbon source of the carbon-modified metal fluoride composite material is one or any combination of carbon nanotubes, carbon black, artificial graphite, natural graphite, acetylene black, graphene and carbon-containing organic polymer materials.
4. The solid-state lithium battery according to claim 3, wherein: The carbon source is one or a combination of carbon nanotubes, carbon black, natural graphite, acetylene black and graphene.
5. The solid-state lithium battery according to claim 1 or 2, wherein: The mass ratio of metal fluoride to carbon in the carbon-modified metal fluoride composite material is 1 to 50:
1.
6. The solid-state lithium battery according to claim 1 or 2, wherein: The solid electrolyte layer comprises a solid electrolyte, and the solid electrolyte is any one or more of a lithium sulfide-containing solid electrolyte, a lithium oxide-containing solid electrolyte, and a lithium polymer-containing solid electrolyte.
7. The solid-state lithium battery according to claim 6, wherein: The lithium sulfide-containing solid electrolyte is selected from Li 10 GeP2S 12 ,Li3PS4,Li3Zn 0.5 GeS4,Li7P3S 11 One or more of the following; the lithium oxide-containing solid electrolyte is selected from Li2Al3Ge2(PO4)3, Li3La2TiO3, LiZr2Ti(PO4)3, Li2Al2Ti(PO4)3 and Li2TaLa3Zr2O 12 One or more of the following.
8. The solid-state lithium battery according to claim 6, wherein: The lithium-containing polymer solid electrolyte is selected from the processed and synthesized product of an organic polymer and a lithium salt, wherein the polymer is one or more of polyethylene oxide, polyacrylonitrile, polymethyl methacrylate, polycarbonate and polyvinylidene fluoride, or the comonomer is a copolymer of two or more of ethylene oxide, acrylonitrile, methyl methacrylate, carbonate and vinylidene fluoride; and the lithium salt is one or more of lithium perchlorate, lithium hexafluorophosphate and lithium bis(trifluoromethanesulfonyl imide).
9. The solid-state lithium battery according to claim 1 or 2, wherein: The positive electrode sheet comprises a positive electrode current collector, a conductive agent, a binder and the positive electrode active material layer.
10. The solid-state lithium battery according to claim 9, wherein: The weight ratio of the conductive agent, the binder and the positive electrode active material layer is (1-10):(1-10):(80-98).
11. The solid-state lithium battery according to claim 10, wherein: The weight ratio of the conductive agent, the binder and the positive electrode active material layer is (2-5):(1-5):(90-97).
12. The solid-state lithium battery according to claim 9, wherein: The conductive agent is one or any combination of conductive carbon black, conductive graphite, conductive carbon nanotubes, graphene and conductive carbon fibers; and / or The binder is one or any combination of polyvinylidene fluoride, polytetrafluoroethylene, polyvinyl alcohol, sodium hydroxymethyl cellulose, polyacrylic acid, styrene-butadiene rubber and acrylonitrile.
13. The solid-state lithium battery according to claim 1 or 2, wherein: The inside of the lithium battery positive electrode plate, the inside of the solid electrolyte layer, between the positive electrode plate and the solid electrolyte layer, and the internal gap of the battery are filled with a non-aqueous electrolyte, and the mass content of the non-aqueous electrolyte in the solid lithium battery is 0.01-5% by weight.
14. The solid-state lithium battery according to claim 1 or 2, wherein: The negative electrode plate is a metal lithium plate and / or a lithium alloy.
Citation Information
Patent Citations
Ferric (III) fluoride / carbon composite material and its preparation method and application
CN103855389A
Preparation method of solid state battery buffer layer and application of solid state battery buffer layer
CN110416637A
All-solid battery
JP2010015782A